Pengaruh Modal Terhadap Pertumbuhan Laba Di PT. Bank Muamalat Indonesia TBK Periode 2015-2022 - Anggriani, Yova; Brahmono, Boris (ADL ISLAMIC ECONOMIC : Jurnal Kajian Ekonomi Islam, 2024)
This study aims to see how capital affects profit growth at Pt Bank Muamalat Indonesia Tbk by using a quantitative research approach muamalat Indonesia Tbk by using a quantitative research approach isecondary data obtained from the Pt Bank Muamalat Indonesia Tbk profile website the approach used to analyze includes a series of statistical tests statistics, such as classical assumption tests, normality tests, multicorrelation tests, heteroscedasticity tests, and hypothesis testing. heteroscedasticity, and hypothesis testing using partial t test and simultaneous f test with SPSS. with SPSS. The results showed that together capital has a positive and significant influence on profit growth in the company, as evidenced by the F test.